2022
DOI: 10.1007/s10661-022-10771-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 impacts on household solid waste generation in six Latin American countries: a participatory approach

Abstract: The COVID-19 pandemic has greatly impacted the Americas, the continent with the highest number of COVID-related deaths according to WHO statistics. In Latin America, strict confinement conditions at the beginning of the pandemic put recycling activity to a halt and augmented the consumption of plastic as a barrier to stop the spread of the virus. The lack of data to understand waste management dynamics complicates waste management strategy adjustments aimed at coping with COVID-19. As a novel contribution to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…This may be related to the global spread of COVID-19 in 2020 and associated lockdowns. A considerable number of waste studies have focused on solid waste generation characteristics [3,111,112] and disposal behaviors [113][114][115] during the pandemic rather than selection and ranking of WDS.…”
Section: Type Of Application On Wds Studies From 2012 To 2021mentioning
confidence: 99%
“…This may be related to the global spread of COVID-19 in 2020 and associated lockdowns. A considerable number of waste studies have focused on solid waste generation characteristics [3,111,112] and disposal behaviors [113][114][115] during the pandemic rather than selection and ranking of WDS.…”
Section: Type Of Application On Wds Studies From 2012 To 2021mentioning
confidence: 99%
“…A recent study by Urbańska et al [ 12 ] found that, at the national level, MSW amounts did not differ much from those of the pre-COVID-19 era. Requena-Sanchez et al [ 13 ] investigated household behaviors in six Latin American countries and found that participants in the study did not report major waste composition changes before or during the pandemic. In summary, numerous studies found that there was more plastic, food, and medical waste generated during the pandemic than there had been before COVID-19.…”
Section: Introductionmentioning
confidence: 99%